2016
DOI: 10.1126/scitranslmed.aad2355
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase inhibitor nanoparticles target tumors with favorable therapeutic index in vivo

Abstract: Efforts to apply nanotechnology in cancer have focused almost exclusively on the delivery of cytotoxic drugs to improve therapeutic index. There has been little consideration of molecularly targeted agents, in particular kinase inhibitors, which can also present considerable therapeutic index limitations. We describe the development of Accurin polymeric nanoparticles that encapsulate the clinical candidate AZD2811, an Aurora B kinase inhibitor, using an ion pairing approach. Accurins increase biodistribution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
140
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 24 publications
8
140
0
Order By: Relevance
“…Recently, there has been a move away from cytotoxic cancer drugs towards molecularly targeted agents (MTAs) that have had little attention in the nanomedicine field. While highly efficacious, these drugs are associated with serious toxicity profiles on their own, and therefore the combination with nanoparticles may help to reduce toxicity and allow higher dosing (43). Next generation BIND micelles that incorporate kinase inhibitors as future drug therapeutics have been used to investigate efficacy against metastatic colon cancers, showing promising results in pre-clinical trials.…”
Section: Polymeric Micellesmentioning
confidence: 98%
“…Recently, there has been a move away from cytotoxic cancer drugs towards molecularly targeted agents (MTAs) that have had little attention in the nanomedicine field. While highly efficacious, these drugs are associated with serious toxicity profiles on their own, and therefore the combination with nanoparticles may help to reduce toxicity and allow higher dosing (43). Next generation BIND micelles that incorporate kinase inhibitors as future drug therapeutics have been used to investigate efficacy against metastatic colon cancers, showing promising results in pre-clinical trials.…”
Section: Polymeric Micellesmentioning
confidence: 98%
“…49 The release kinetics of encapsulated drug has significant impacts on the efficacies of drug delivery systems. 49, 50 Burst release would result in similar pharmacokinetics between encapsulated drug and a free form of drug, diminishing advantages of using NP as a drug carrier. Hence, the sustained release of Gi would benefit in vivo application.…”
Section: Resultsmentioning
confidence: 99%
“…Barasertib has entered clinical trials in elderly patients with acute myeloid leukaemia (AML) and has demonstrated clinically meaningful responses, including complete remission in some patients [36,37]. In 2013, an agreement was signed with BIND Therapeutics to further develop the active ingredient of AZD1152 (AZD1152-hQPA, recently designated AZD2811 (compound 18) [38] using Accurin 1 nanoparticle technology and offering the potential to adapt the therapeutic regimen to different tumours while achieving an improved therapeutic index. AZD2811 has recently commenced Phase I clinical testing in patients with advanced solid tumours.…”
Section: Inhibitor Of Aurora-b Kinase Barasertibmentioning
confidence: 99%